1972
DOI: 10.1161/01.res.30.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Hyperplasia and Hypertrophy in Cardiomegalies Induced by Anemia in Young and Adult Rats

Abstract: In our previous studies a twofold cardiomegaly associated with a proportional increase in cardiac DNA was found in rats subjected to a low-iron diet after weaning. To localize the newly synthesized DNA, control and anemic rats 24-34 days of age were given three intraperitoneal injections of 3 Hthymidine (1 /Ac/g body weight; 22c/mM) at 2-hour intervals. The radioautographs were prepared from sections of the left ventricle stained with PAS-hematoxylin. Between 26 and 34 days of age, significantly larger numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(26 citation statements)
references
References 24 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…In contrast, a hyperplastic component has been observed in cardiac enlargement produced in neonatal animals by nutritional anemia ( 12) or after aortic constriction in rats at 3 wk of age (13). There is only one experimental documentation of myocyte nuclei hyperplasia in the adult rat heart found in hypertrophied atrial tissue early after infarcts of the left ventricle (14).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a hyperplastic component has been observed in cardiac enlargement produced in neonatal animals by nutritional anemia ( 12) or after aortic constriction in rats at 3 wk of age (13). There is only one experimental documentation of myocyte nuclei hyperplasia in the adult rat heart found in hypertrophied atrial tissue early after infarcts of the left ventricle (14).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators also have found that if the despite pooling, norepinephrine and DNA polymerase assays cardiovascular system of the newborn animal is stressed, e.g., by could not be determined in the same animals. Selection of pups altered nutrition (16) or anemia (24), increased myocardial muscle was random for DNA polymerase assay (144 control and 138 6-cell hyperplasia may occur. However, in the adult animal, myo-OHD) and for the norepinephrine assay (98 control and 101 6-cardial muscle cell hypertrophy and connective tissue hyperplasia OHD).…”
Section: Effective Sympathectomy Was Verified By Identifying a Decreamentioning
confidence: 99%
“…However, in the adult animal, myo-OHD) and for the norepinephrine assay (98 control and 101 6-cardial muscle cell hypertrophy and connective tissue hyperplasia OHD). occur, but muscle cell hyperplasia has not been demonstrated (10,24,29).…”
Section: Effective Sympathectomy Was Verified By Identifying a Decreamentioning
confidence: 99%
“…In both the control and experimental groups of rats, DNA problem (1,6,10,16,20,(24)(25)(26). Studies in the rat have shown polymerase and ventricular norepinephrine assays were carried that myocardial cell division continues after birth, but gradually out at Cday intervals beginning at 4 days of age.…”
Section: Effective Sympathectomy Was Verified By Identifying a Decreamentioning
confidence: 99%
See 1 more Smart Citation